EXPLORING ETHICAL CONTINUITY: A COMPARATIVE ANALYSIS OF APOLOGY AND LETTER FROM BIRMINGHAM JAIL - Ernawati, Asih; Riyatno , Riyatno (DE FACTO : Journal Of International Multidisciplinary Science, 2024)
This article examines the enduring relevance of Socrates' "Apology" and Martin Luther King Jr.'s "Letter from Birmingham Jail," highlighting their shared commitment to justice and ethical integrity despite the vast differences in their historical and socio-political contexts. Both texts employ powerful rhetorical strategies to advocate for truth and moral righteousness, challenging deeply ingrained societal injustices. Socrates, through his dialectical method, exposes the inconsistencies in his accusers' arguments, encouraging critical self-examination, while King, through logical reasoning and emotional appeals, compels his audience to confront the moral failings of their society. The thematic connections between the two works, particularly their emphasis on truth, moral integrity, and the courage to challenge unjust laws, underscore their timeless significance in the discourse on moral philosophy and social justice. By situating their arguments within broader ethical and intellectual traditions, both Socrates and King provide timeless models of ethical leadership and moral courage. Their works continue to resonate, offering profound insights into the ongoing struggle for a more just and equitable world, making their messages relevant for contemporary movements against injustice and oppression.